2021
DOI: 10.21273/hortsci15700-21
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Responses of Ornamental Grasses to Saline Water Irrigation

Abstract: Reclaimed water provides a reliable and economical alternative source of irrigation water for landscape use but may have elevated levels of salts that are detrimental to sensitive landscape plants. Landscape professionals must use salt-tolerant plants in regions where reclaimed water is used. Ornamental grasses are commonly used as landscape plants in the Intermountain West of the United States due to low maintenance input, drought tolerance, and unique texture. Six ornamental grass species, including Acorus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…By the second harvest, the substrate EC increased to 5.11, 9.66, 15.77, and 31.10 dS•m À1 for the corresponding salinity treatments. Consistent with findings in various studies (Paudel et al 2019;Sun and Palmer 2018;Sun et al , 2020Xing et al 2021) using peat-based soilless growing substrate, both leachate and substrate EC increased over time with saline solution irrigation. This rise in leachate and substrate EC reflects the accumulation of salts in the substrate, directly correlating with the observed damage to the plant foliage.…”
Section: Resultssupporting
confidence: 89%
“…By the second harvest, the substrate EC increased to 5.11, 9.66, 15.77, and 31.10 dS•m À1 for the corresponding salinity treatments. Consistent with findings in various studies (Paudel et al 2019;Sun and Palmer 2018;Sun et al , 2020Xing et al 2021) using peat-based soilless growing substrate, both leachate and substrate EC increased over time with saline solution irrigation. This rise in leachate and substrate EC reflects the accumulation of salts in the substrate, directly correlating with the observed damage to the plant foliage.…”
Section: Resultssupporting
confidence: 89%
“…In most situations, high salinity leads to osmotic stress and ion toxicity in plants, which is reflected in slow growth and wilting of leaves [32]. Similar conclusions were presented in recent studies, such as the plant heights of six ornamental grasses (Acorus gramineus, Andropogon ternarius, Calamagrostis × acutiflora, Carex morrowii, Festuca glauca, and Sporobolus heterolepis) all reduced when the EC of salt solution exceeded 5 dS•m −1 , and S. heterolepis was more stabilized than other species in different salt treatments, which indicated less salt-sensitive characteristics [33]. With the salt treatment in 5 dS•m −1 and 10 dS•m −1 , the growth of Calendula officinalis was restricted by the decline in the percentage of dry matter [34].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Wu et al (2016) and Xing et al (2021) reported that leachate and substrate EC increased with saline water irrigation over time as salts accumulated in the substrate. Salt accumulation is a potential problem when poorquality saline water is used for landscape irrigation.…”
Section: Resultsmentioning
confidence: 85%